Breeding of Sand Goby, Oxyeleotris marmorata (Blkr'), Broodstock in Earthen and Concrete Pond - Sumawidjaja, Kusman; Effendi, Irzal; Enywati, . (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTAnexperiment to asses breeding performance of sand goby was conducted in earthen and concrete pond. Broodstock (125 - 500 g per fish) of similar levels at maturing were fed trash fish 7% of biomass everyday. In the rainy season, sand goby, Oxyeleotris marmorata (Blkr.), spawned 31 and 30 times per month producing an average of 38.300 and 36.855 eggs per nest, respectively. In the dry sesason, howeve only fish in earthen ond bred 36 times per month with an average of 39.170 eggs per nest.Key words : breeding, sand goby fish, Oxyeleotris marmorata ABSTRAKPercobaan ini bertujuan untuk mengetahui pemijahan ikan betutu di kolain tanah dan kolarn beton. Ikan betutu (125 - 500 g per ekor) dipelihara selarna musim hujan dan musim kemarau dan diberi makan ikan teri sebanyak 7% setiap hari. Pada musim penghujan, pada kolam tanah dan kolam beton terjadi masingmasing 31 dan 30 kali pemijahan ikan betutu, Oxyeleotris marmorata (Blkr.), per sarang. Pada musim kemarau, hanya ikan betutu yang di kolam tanah saja yang memijah sebanyak 36 kali dengan rata-rata 39.170 butir per tahun per sarang.Kata kunci : pemijahan, ikan betutu, Oxyeleotris marmorata